Designing Microsoft Azure Infrastructure Solutions (AZ-305) - Gordon, Adam (Packt Publishing Ltd., 2024)
Dive into the essentials of designing robust cloud infrastructure with Microsoft Azure. This comprehensive course guides you through the complexities of solution design, from log routing and monitoring tools to securing resources and identity management. Enhance your understanding of hierarchical resource management, compliance enforcement, and Azure's organizational structure, preparing you for advanced architectural challenges. Transition to advanced modules that cover the integration of applications with Azure AD, database scalability, and data protection strategies. Each lesson is crafted to build on your knowledge, focusing on practical applications and real-world scenarios that Azure architects face daily. This structured approach ensures a thorough understanding of each concept, from security to compliance and data storage solutions. Conclude your learning journey by mastering recovery solutions for diverse environments, high availability strategies, and advanced compute solutions including virtual machines, containers, and serverless options. The course's capstone sections on network architecture provide key insights into optimizing performance and security, equipping you with the skills to design and implement comprehensive Azure solutions effectively.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Azure (Computing platform) -- Study guides -- Examinations; Cloud computing -- Study guides -- Examinations; Microsoft Azure (Plateforme informatique); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet